Performing rapid metabolite tests (IgG-IgM) for SARS-CoV-2 infection in community pharmacies: A cross sectional-study from Brazil (Pharmacy Practice, 2023)
Background: Immunochromatographic rapid tests in pharmacies allow the discovery of specific antibodies against SARS-CoV-2 or viral antigens and provide a broader and more effective screening of the virus. However, in many countries, this process is still not well defined. In this sense, the perception of pharmacists about these screening practices presents an overview of how the service is being carried out in the country. Objective: This study was to evaluate the performance of rapid immunochromatographic tests and their clinical results in community pharmacies in northern Brazil. Method: A retrospective study was carried out between May 2020 and December 2021 in community pharmacies in the northern region of Brazil. Participants were 18 years of age or older, of both sexes, who spontaneously sought the SARS-CoV-2 rapid testing service at pharmacies located in the municipality of Belem and who had had close contact with the virus or symptoms infection-related. Data were expressed as median and range or as frequency of occurrence. Chi-square t-test and Fisher’s exact test were used to compare variables. The accepted significance level was 5%. This study was approved by the Research Ethics Committee (number: 4,865,206). Results: A total of 78,849 patients were recruited into the study. Most patients, 37,847 (48%), were tested antibody positive for SARS-CoV-2. There were no severe signs and symptoms of the disease. The results showed the great demand for carrying out the rapid test in pharmacies and these places could contribute to the understanding of this health establishment, to curb the speed of SARS-CoV-2 dissemination. Conclusion: This study showed the demand for rapid tests for SARS-CoV-2 in pharmacies, as well as the large number of patients identified with the disease. Thus, these places must exercise a workforce and obtain organized actions to collaborate with the rest of the health system, reducing the overload of urgent and emergency units, as well as the risk of contamination that seek them